The Entrepreneurs Potential of Car Rental Business for Tourism in Songkhla Province and Linkage Areas - Jankingthong, Korkaew (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
The objectives of this research were 1) to assess the entrepreneurs’ potential of car rental business for tourism in Songkhla province and linkage areas 2) to compare the entrepreneurs’ potential of car rental business for tourism in Songkhla province and linkage areas by personal factors and 3) to analyze the SWOT Analysis of the car rental business for tourism in Songkhla province and linkage areas. A mixed method study was used in this study. The sample was 385 entrepreneurs of car rental in quantitative research while the sample size used in qualitative method was 35 persons. Statistics used for data analysis were percentage, arithmetic mean, standard deviation and One-way ANOVA. The results revealed that the entrepreneurs of car rental business for tourism in Songkhla province and linkage areas had a high potential overall. As for the entrepreneurs’ potential of car rental business for tourism in Songkhla province and linkage areas by personal factors, it was found that the entrepreneurs with different ages had the potential for vehicle perfection, management, accident management, environmental management, and services differently. Also found that the entrepreneurs with different educational levels had the potential for vehicle perfection, management, accident management, and environmental management differently.